FORMULASI DAN EVALUASI FISIK SEDIAAN KAPSUL EKSTRAK DAUN CINCAU HIJAU (Cyclea barbata Miers ) SEBAGAI ANTI INFLAMASI - Fitria Wulandari; Fitri Wahyu Widyawati; Khusnul Rizaldi; Fauzia Ningrum Syaputri (Fakultas Farmasi UMI, 2020)
One of the Indonesian plants that can be used is green grass jelly leaf (Cyclea barbata Miers) because it contains alkaloids, polyphenols, saponins and flavonoids that can prevent inflammation. Inflammation is an environmental physiological response caused by damage or damage to the tissue that functions, reduces, or confines an injuring agent or injured tissue. The purpose of this study was to formulate green grass jelly leaf extract into anti-inflammatory capsules. This research begins with the maceration of the simplicia extraction process of green grass jelly leaves using ethanol 96% solvent. Granule preparation used dry granulation method with vivapur 101 which varied in 3 formulas, namely (1: 1, 1: 1,5, 1: 2). The next step was a physical evaluation test of granules including moisture content, flow properties, angle of rest, carcass index, compressible density and true density and a physical evaluation test including organoleptic test, weight uniformity and disintegration time. The results of the evaluation test that have been carried out show that formula 3 with a thick extract concentration: vivapur 101 (1: 2) is the most optimal, because it meets the evaluation test requirements with a moisture content value of dry extract granules 1.5% and a water content value of granule capsules. green grass jelly leaves 1.1%.